2005
DOI: 10.1079/bjn20051478
|View full text |Cite
|
Sign up to set email alerts
|

Obesity induced during sexual maturation is linked to LDL-triacylglycerols in Yucatan miniature swine

Abstract: The incidence of childhood obesity is rising dramatically throughout industrialised countries. To evaluate and study the impact of childhood obesity on lipoprotein metabolism, we developed a new animal model of premature obesity. Yucatan mini-pigs aged 4 months were studied over a 12-month period from childhood to adulthood. Animals were divided into two groups: the first group were overfed a Western misbalanced diet; the second group were normally fed a recommended human-type diet. Cholesterol and triacylglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
(55 reference statements)
1
9
2
Order By: Relevance
“…Similar to other studies in IUGR models (Poore et al 2002;Woods and Weeks 2004), previous data from our mini-pig model showed that IUGR was associated with higher blood pressure and salt sensitivity in early adulthood (Myrie et al 2011;Myrie et al 2012a). Because the pig is one of the most relevant species for modeling lipoprotein metabolism in humans (Larsen et al 2002;Sébert et al 2005;Torres-Rovira et al 2012), the objective of this study was to evaluate the effects of birth weight, as a proxy for IUGR, on lipid metabolism and endothelial function as indicators of cardiovascular disease risk in a Yucatan miniature pig model.…”
supporting
confidence: 87%
“…Similar to other studies in IUGR models (Poore et al 2002;Woods and Weeks 2004), previous data from our mini-pig model showed that IUGR was associated with higher blood pressure and salt sensitivity in early adulthood (Myrie et al 2011;Myrie et al 2012a). Because the pig is one of the most relevant species for modeling lipoprotein metabolism in humans (Larsen et al 2002;Sébert et al 2005;Torres-Rovira et al 2012), the objective of this study was to evaluate the effects of birth weight, as a proxy for IUGR, on lipid metabolism and endothelial function as indicators of cardiovascular disease risk in a Yucatan miniature pig model.…”
supporting
confidence: 87%
“…In this study, feeding a HED with no extra cholesterol added led to moderate increases in TG, TC, and HDL‐C, but did not affect HLD‐C ratio. The diet‐induced changes in plasma lipids were present both before and after sexual maturity, which is interesting, since another study with young male Yucatan minipigs failed to show similar effects despite a comparable increase in BW (31).…”
Section: Discussionmentioning
confidence: 80%
“…The changes in glucose and lipid metabolism were apparent already after a few weeks of diet feeding, indicating that the recent change from a low energy diet to a high energy diet in itself was sufficient to shift the metabolism independent of vast changes in body fat measures. It is thus possible to acutely induce metabolic impairments in juvenile growing Göttingen minipigs using only moderate dietary intervention, which is in contrast to what has been observed in young Yucatan minipigs (31,36). Surprisingly, the metabolic parameters did not seem to deteriorate further with prolonged diet feeding, despite significant increases in all body fat measures.…”
Section: Discussionmentioning
confidence: 87%
“…The changes in glucose and lipid metabolism were apparent already after a few weeks of diet feeding, indicating that the recent change from a low energy diet to a high energy diet in itself was sufficient to shift the metabolism independent of vast changes in body fat measures. It is thus possible to acutely induce metabolic impairments in juvenile growing G€ ottingen minipigs using only moderate dietary intervention, which is in contrast to what has been observed in young Yucatan minipigs (31,36). Surprisingly, the metabolic parameters did not seem to deteriorate further with prolonged diet feeding, despite significant increases in all body fat measures.…”
Section: Obesitymentioning
confidence: 88%